Mycoflora associated with stored rice from storage facilities in Makassar and Maros, Indonesia - EIRENE BRUGMAN; M. BAYU MARIO (Society for Indonesian Biodiversity, 2024)
Abstract. Brugman E, Mario MB. 2024. Mycoflora associated with stored rice from storage facilities in Makassar and Maros, Indonesia. Biodiversitas 25: 1089-1096. Rice storage is a postharvest process that aims to maintain food availability, seed supply, and price stability. One of the main problems encountered in the storage process is the potential for fungal infection and contamination, leading to postharvest loss. This research aims to evaluate the mycoflora associated with stored rice from storage facilities in Makassar and Maros and their contamination level. Fungal isolation was done by spread plating with serial dilution and direct culture method. The fungal identification was made based on morphological characters, including colony, sexual, and asexual structures. The fungal contamination was determined by colony counting, contamination percentage, and species occurrence. The result showed that all samples tested positive for fungal contamination, with an average contamination level of 83.89% (Makassar) and 86.11% (Maros). The highest colony densities in the samples from Makassar and Maros were 9.0 × 103 CFU/g and 14.2 × 103 CFU/g, respectively. The average fungal contamination in the samples from Makassar was 3.67 × 103 CFU/g, and Maros was 8.32 × 103 CFU/g. The mycoflora associated with the rice grain samples from Makassar was Rhizoctonia solani (11.34%), Aspergillus spp. (52.18%), Fusarium spp. (10.87%), Rhizopus sp. (15.22%), and unidentified cultures (10.39%). Meanwhile, the mycoflora associated with the stored rice from Maros are Curvularia sp. (15.22%), Alternaria sp. (8.7%), Aspergillus spp. (17.39%), Fusarium spp. (32.61%), Rhizopus sp. (15.22%), and Bipolaris oryzae (10.87%).